Use of social networks and its relationship with positive behavior among public and private kindergarten children from the perspective of teachers in Sulaimani - Mohammed, Vian Ahmed Mohammed; Khalid, Prof.Dr.Husain Fakhruddin Khalid (Sulaimani Journal for Humanities, 2025)
The aim of this study is to find out the level of social media use and its relationship with positive behavior among kindergarten children from the teachers' point of view according to the hours of use, and the difference between kindergartens (public and private). The research population consists of all teachers of public and private kindergartens in Sulaimaniyah for the academic year 2024-2025. The number of teachers is 1,408 out of that 156 being male teachers and 1,252 female teachers. A sample of 454 teachers, from both genders, was selected through simple random sampling, and the tool used was a scale measuring) social media usage and positive behavior( .The main statistical tools used are SPSS (version 25), Pearson correlation, construct reliability, and finding the relationship between variables, Cronbach's alpha, independent sample T-test, independent sample T-test, independent sample T-test, one-sample T-test, and using one-way ANOVA. The researchers used a questionnaire tool for data collection, which consists of 45 items. As a result, it was found that the use of social networks and the relationship with positive behavior in kindergarten children from the teachers' perspective based on usage of (1-3 hours) is at a good level. Additionally, there is a statistical difference in the level of social media usage and its relationship with positive behavior, depending on the type of kindergarten. From the teachers' perspective, kindergarten children's use of social media in relation to positive behavior is low, as they spend approximately 4-6 hours on it.
Keywords: Social Media; Positive Behavior; Kindergarten; Children in kindergarten; Child